(untitled) (Research, Society and Development, 2021)
This study aimed to characterize the centesimal composition of the fruit of the currioleira (Pouteria ramiflora) and to verify the physicochemical and sensorial characteristics of the fruit liqueurs. The levels of moisture, dietary fiber, protein, lipids, ashes and carbohydrates and the energetic value of fruit pulp were quantified. Liqueurs of pulp and whole fruit were prepared with sugar concentrations of 150 and 250g.L-1. The liqueurs were submitted to sensory analysis of acceptance and purchase intention and determined the alcohol content, total acidity, pH, soluble solids, color parameters, total phenolic compounds and antioxidant capacity. In the centesimal composition of the curriola pulp, the high fiber content is 12.75g.100g-1 and low calorie 54.11kcal.100g-1. Significant differences p<0.05 were observed in the liqueurs in the physical-chemical and sensorial analyzes of the liqueurs. Pulp liqueurs obtained a higher intensity of yellow with averages of b* 44.36 and 44.42 and tended to color green with negative values of a* -0.89 and -1.87, in contrast, whole fruit liqueurs presented a higher degree of red with positive values of a* 9.60 and 5.43. The color of pulp liqueurs was less accepted (4.23 and 4.32) in relation to the liqueurs of the whole fruit (5.46 and 5.46). The alcoholic concentrations of 20.58, 22.75, 33.58 and 42.75 influenced the overall impression, taste and intention to buy liqueurs. The liqueurs of the curriola fruit can reach better acceptance and purchase intention with the decrease of the alcoholic content.